2015
DOI: 10.7150/jca.10398
|View full text |Cite
|
Sign up to set email alerts
|

Problems of Long Survival Following Surgery in Patients with NonBNonC-HCC: Comparison with HBV and HCV Related-HCC

Abstract: Background: The number of patients with hepatocellular carcinoma (HCC) in the absence of both hepatitis B virus surface antigen (HBsAg) and hepatitis C virus antibody (HCVAb) (NBNC-HCC) has been rapidly increasing in Japan. The objective of this study was to compare the clinical and pathological characteristics between patients with the NBNC-HCC, those with HBsAg positive HCC (B-related HCC) and HCVAb positive HCC (C-related HCC). A better understanding will facilitate the development of postoperative strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
2
9
0
1
Order By: Relevance
“…33 In a Japanese study with 219 HCC patients, the prognostic factors were different according to the background liver diseases. 34 The condition of the underlying liver in HCC patients is one of the most important factors to decide treatment modality as well as to alter the survival outcomes. Although HCC most commonly occurs in the cirrhotic liver, approximately 10 to 40 % of cases develop against non-fibrotic to moderately fibrotic parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…33 In a Japanese study with 219 HCC patients, the prognostic factors were different according to the background liver diseases. 34 The condition of the underlying liver in HCC patients is one of the most important factors to decide treatment modality as well as to alter the survival outcomes. Although HCC most commonly occurs in the cirrhotic liver, approximately 10 to 40 % of cases develop against non-fibrotic to moderately fibrotic parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of recurrence and low rate of OS after hepatectomy in preoperative neutrophil-to-lymphocyte ratio, and other factors. [7][8][9][10] Because prealbumin reflects liver functional levels, 4,11 we examined its ability to predict OS after hepatectomy in a cohort of patients treated at our hospital. We found that it may be useful for predicting prognosis, and this finding was robust to subgroup analyses based on several clinicopathological variables.…”
Section: Discussionmentioning
confidence: 99%
“…Recently researchers have opined that long non-coding RNA PVT1 is associated with tumor progression and is a significant predictor of recurrence in liver cancer patients [9]. Contrarily, reports indicate that in patients with NBNC-HCC profile (patients with HCC in absence of both hepatitis B virus surface antigen, HBsAg and hepatitis C virus antibody, HCVAb), elevated serum bilirubin could predict poor recurrencefree survival after surgery [10]. Studies have also revealed low serum IL-6 level to be an independent prognostic factor for disease-free survival together with low platelet count and low serum albumin level, in patients with HBVrelated early HCC who underwent hepatic resection or radiofrequency ablation with a curative intent [11].…”
Section: Introductionmentioning
confidence: 99%